Antiviral activity of Ribavirin nano-particles against measles virus - Ahmed, Engy M; Solyman, Samar M; Mohamed, Noha; Boseila, Abeer A; Hanora, Amro (Cellular and Molecular Biology, 2018)
Measles virus considers an important cause of child morbidity and mortality in some areas as Africa. Ribavirin’s activity as a nucleoside analog can disclose the surprisingly broad spectrum action against several RNA viruses under laboratory cell culture conditions. The Current study aimed to investigate the antiviral activity of ribavirin Nano gold particles (AuNPs) against measles virus on vero cell line. Ribavirin- AuNPs was prepared, characterization and the cytotoxicity of ribavirin, AuNPs and ribavirin -AuNPs were tested on vero cells using MTT assay. Antiviral activiry of ribavirin, AuNPs and ribavirin- AuNPswere determined on vero cells using simultaneous, pre-infection and post-infection protocols. Results indicated safety of ribavirin and ribavirin-AuNPs on vero cells, there was a reduction by 78.1% when vero cells treated with ribavirin -AuNPs at 99.5µg/ml while, the viral reduction was 25.4% when ribavirin 500 µg /ml was used for the same viral concentration. Our results concluded that ribavirin - AuNPs had a higher antiviral activity with lower dose than ribavirin alone and the maximal activity showed when it used after the virus infection.